ANALISA MIKROBIOLOGI CEMARAN BAKTERI COLIFORM DAN SALMONELLA SP PADA TAHU DI KECAMATAN DELTA PAWAN - Nenengsih Verawati; Nur Aida; Ridha Aufa (Jurnal Teknologi Agro-Industri, 2019)
Tofu is a high-protein soy-based food ingredient that is widely consumed in Indonesia. Tofu producers in Delta Pawan Subdistrict are dominated by small and medium-sized entrepreneurs whose hygiene and sanitation aspects in production activities are very under-taken. This study aims to determine the presence of Coliform and Salmonella Sp bacteria on tofu produced in Delta Pawan sub-district, Ketapang, West Kalimantan and compare with SNI01-3142-1998. The method used to detect the presence of Coliform bacteria in this study uses the Most Probable Number (MPN) method, which consists of estimator and confirmatory tests using Lactosa Broth (LB) media for the Brilliant Green Lactose Broth (BGLB) assay test for confirmation . Whereas to detect the amount of Salmonella Sp using the method of Total Plate Count (TPC) with selective media Salmonella Shigella Agar (SSA). The results of Coliform analysis in both industries found Coliform MPN values ​​of more than 2400 AMP / g samples, which indicated that they did not meet the standards set by SNI. While the results of the analysis of Salmonella Sp obtained positive results, so the two industries did not meet food safety standards.